Blended Chinese language learning design: an integrative review and synthesis of the literature. Issue 3 (27th May 2019) - Hughes, Neil; Lo, Lan; Xu, Sujing
ABSTRACT: This paper addresses a number of questions in the emerging area of blended Chinese language learning design. First, what are the strengths and weaknesses of the extant literature? Second, how might insights from the wider blended and blended language learning literature advance the field? Third, how might these literatures be synthesised to produce a set of parameters for effective blended Chinese language learning design? Fourth, what might a course based on these parameters look like in practice? The review of relevant literature, identified via a Google Scholar search, is carried out using an integrative literature review methodology. This approach proves a useful vehicle for critically evaluating the state of the literature and for developing practical guidance for blended Chinese language learning designers based on a synthesis of findings from the review with valuable insights from the wider blended language learning research. The design parameters that emerge from this process (mode, integration, research, asynchronicity, challenges, learners and evaluation, with the initial letter of each of the parameters providing the acronym MIRACLE) are discussed in turn and their applicability demonstrated using examples from a beginners' Chinese language course delivered at the University of Nottingham in the UK.